BIOSIMILAR MEDICINE PRICE ANALYSIS IN BRAZIL: THE ANTIRHEUMATIC CASE - GONZALEZ MOSEGUI, GABRIELA BITTENCOURT; VILLAR, FERNANDO ANTOÑANZAS; VIANNA, CID MANSO DE MELLO; GARCIA ROJAS, PAULA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The introduction of biosimilar medicines in markets can bring savings to health systems, expanding the population’s access to various treatments. This study aims to analyze the price competition of biological agents and their biosimilars in Brazil within the scope of rheumatoid arthritis. Methods: Prices for 14 presentations of original and biosimilar medicines were analyzed from January 2003 to October 2019 in Brazil. Prices were taken from official lists and were noted since launch and during the later trading period. Prices were converted to United States dollars and adjusted for inflation for the 2003 base year. Results: In Brazil, during this review period, prices of biopharmaceuticals decreased in real values, reaching up to a 50% reduction. The introduction of biosimilars did not affect the price sharing of biological medicines. Conclusion: Biosimilar antirheumatics do not yet have a significant impact on the price of biologics marketed in Brazil. A change in this scenario is expected in the medium and long term.